PWE-310 Extramural vascular invasion is a more powerful predictor of prognosis than tumour regression grade in rectal cancer. (22nd June 2015) - Palkhi, E; Harji, D; Pathak, S; Burke, D; Sagar, P
Abstract : Introduction: There are a number of pathological predictors of adverse outcome in rectal cancer which includes positive resection margin, extramural vascular invasion (EMVI) and tumour regression grade (TMG). The aim of this study is to elicit the prognostic significance of EMVI and TMG for primary rectal cancer. Method: All patients undergoing surgery for primary rectal cancer were identified from a prospectively maintained database between 2004 and 2012. Tumours were graded using a quantitative 5-grade Mandard TRG classification and the presence of EMVI was histologically studied. Results: A total of 342 patients were identified, of which 99 patients had a complete dataset for EMVI and TRG. The 5-year overall survival (OS) was 38% with a disease-free survival (DFS) of 72%. Poor TRG grades and EMVI positivity were found to prognostically significant for OS (p values 0.01 and 0.05, respectively) and DFS (p values 0.02 and 0.001, respectively) at univariate analysis. However, EMVI positivity remained statistically significant for OS (p = 0.05) and DFS (p = 0.01) at multivariate analysis over TRG (OS, p = 0.46 and DFS, p = 0.17). Conclusion: The presence of EMVI is a more powerful prognostic factor than TRG in rectal cancer and should be taken into account during the risk stratification process when considering adjuvant chemotherapy. Disclosure of interest: None Declared.